Multiple endocrine neoplasia type 1 caused by mosaic mutation: clinical follow-up and genetic counseling?. Issue 1 (24th May 2022) - Coppin, Lucie; Giraud, Sophie; Pasmant, Eric; Lagarde, Arnaud; North, Marie-Odile; Le-Collen, Lauriane; Aubert, Valérie; Mougel, Grégory; Ladsous, Miriam; Louboutin, Alyzée; Brixi, Hedia; Haissaguerre, Magalie; et al.
Abstract: MEN1 is an autosomal dominant hereditary syndrome characterized by several endocrine tumors, in most cases affecting the parathyroid glands, pancreas, and anterior pituitary. It is the result of inactivating mutations in the tumor suppressor gene MEN1 . More than 1300 different mutations have been identified in this gene. Mosaic MEN1 mutations have been previously described in only a few patients in the literature. In this paper, we provide a review of six cases of MEN1 mosaicism reported in the literature supplemented with six additional cases described by the French TENgen network of laboratories. This review highlights that (i) MEN1 mosaicism is not associated with a mild phenotype and results in the same natural history as heterozygous MEN1 mutation and (ii) that more systematic detection of MEN1 mosaic mutation enables improvements in both patient monitoring and genetic counseling.